A efficient, metal-free and sustainable synthesis, C-S linked by simple C-H thiocyanation of 4-aminocoumarin or 4-(N-aryl)aminocoumarin derivativess. (21st March 2023) - Askarzadeh, Mohammad; Moazzam, Ali; Vojdanitalab, Khashayar; Hosseini, Samanesadat; Adib, Mehdi; Mahdavi, Mohammad
Abstract: In the present study, we describe the successful development of a novel and efficient C(sp 2 )−H thiocyanation reaction of 4-aminocoumarin and 4-( N -aryl)aminocoumarin derivatives with readily available using KSCN as thiocyanating agent and K2 S2 O8 as an oxidant in ACN under the air atmosphere and room temperature. The most notable point, the reaction proceeded smoothly without the addition of any metal catalyst or strong oxidant and heat, ultimately minimizing the production of chemical waste. The advantages of this reaction met the requirements of green and sustainable synthetic chemistry and may be widely used in organic synthesis and pharmaceutical chemistry. Graphical abstract: Image 1